Study the effect of doping process on the PMOS structure using silvaco TCAD tools / Aida Zulia Zulhanip - Zulhanip, Aida Zulia (2007)
This paper presents the study on the effect of doping process on the PMOS structure using Silvaco TCAD Tools. This research done by dope the P-type material into the polysilicon to observe the electrical properties and performance of PMOS structure at constant dose concentration of 3.0el I (/cm5) and temperature to 950 °C using Silvaco TCAD Tools Software. By choosing the P-type materials such as Boron and Gallium, the result due to electrical performance will be appearing in the graph of ID versus VG and Id versus VD graph in Atlas Device Simulation. To study the material penetration and depletion, the graph of concentration (/cm3) versus depth (p.m) will be shown in Tony plot structure. Both of these results are needed to compare the suitable materials used in conducting electricity of PMOS. Dopant material doped in polysilicon will provide the advantage of a good ohmic contact with the wafer silicon and can be oxidized to form an insulating layer.